Non-random arrangement of nucleosomes in satellite I containing chromatin of rat liver. - Igo-Kemenes, T (1980)
The location of nucleosomes on the nucleotide sequence of rat satellite I DNA was investigated using micrococcal nuclease, exonuclease III, and restriction nucleases as tools. Hae III cleaved the satellite DNA containing chromatin very preferentially in the linker region. Nucleosomes were found predominantly in three defined positions on the 370 bp satellite I monomer unit. This type of arrangement occurs on not more than half of the satellite DNA containing chromatin while the rest of this chromatin is arranged differently. The arrangement of nucleosomes with high probability in preferred frames and with low probability in less preferred frames may be a general phenomenon which can be discussed as a possible mechanism to modulate sequence recognition.